2005
DOI: 10.1523/jneurosci.0328-05.2005
|View full text |Cite
|
Sign up to set email alerts
|

Truncated Prion Protein and Doppel Are Myelinotoxic in the Absence of Oligodendrocytic PrPC

Abstract: The cellular prion protein PrP C confers susceptibility to transmissible spongiform encephalopathies, yet its normal function is unknown. Although PrP C -deficient mice develop and live normally, expression of amino proximally truncated PrP C (⌬PrP) or of its structural homolog Doppel (Dpl) causes cerebellar degeneration that is prevented by coexpression of full-length PrP C . We now report that mice expressing ⌬PrP or Dpl suffer from widespread leukoencephalopathy. Oligodendrocyte-specific expression of full-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
75
0
1

Year Published

2007
2007
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(83 citation statements)
references
References 64 publications
7
75
0
1
Order By: Relevance
“…Prnp knockout mice overexpressing the C-terminal portion of PrP c (lacking OR and CD) of the N-terminal domain (F35 mice) display CGN death, white matter pathology and a progressive and early lethal ataxic phenotype termed Shmerling syndrome (Radovanovic et al, 2005;Shmerling et al, 1998). PCs present no signs of degeneration because of enhancer-mediated splicing that prevents F35 expression in these neurons (Shmerling et al, 1998).…”
Section: Other Prp C Mutant Mice: the Puzzle Of Functions Increasesmentioning
confidence: 99%
See 2 more Smart Citations
“…Prnp knockout mice overexpressing the C-terminal portion of PrP c (lacking OR and CD) of the N-terminal domain (F35 mice) display CGN death, white matter pathology and a progressive and early lethal ataxic phenotype termed Shmerling syndrome (Radovanovic et al, 2005;Shmerling et al, 1998). PCs present no signs of degeneration because of enhancer-mediated splicing that prevents F35 expression in these neurons (Shmerling et al, 1998).…”
Section: Other Prp C Mutant Mice: the Puzzle Of Functions Increasesmentioning
confidence: 99%
“…Similarly to Dpl-mediated degeneration, Shmerling syndrome is rescued by reintroducing the full-length Prnp (Shmerling et al, 1998). However, it has been proposed that myelin pathology induced by N-terminally truncated PrP c acts through independent mechanisms, in contrast to CGN depletion (Radovanovic et al, 2005). Recent studies have shown that overexpression of PrP c devoid of CD or a fragment of CD (residues 105-125) in PrP c knockout mice promotes an exacerbated ataxic syndrome, causing lethality at approximately postnatal day 20 (Baumann et al, 2007;Li et al, 2007b).…”
Section: Other Prp C Mutant Mice: the Puzzle Of Functions Increasesmentioning
confidence: 99%
See 1 more Smart Citation
“…This abnormality, which was also seen Tg(Δ32-134) mice (Radovanovic et al, 2005), may be due either to axonal or myelin damage.…”
Section: Neurotoxicity Of Prp Deletion Mutantsmentioning
confidence: 66%
“…21,22 Of particular note, these deletion mutants show degeneration of axons and myelin, both in the CNS and in peripheral nerves; indeed some mutants show a predilection for axomyelinic degeneration with little neuronal pathology, 21 suggesting that certain mutated forms of PrP have a direct toxic effect on oligodendrocytes and/or myelin. 23 Moreover, activation of the Dpl1 gene in mice lacking PrP C leads to an ataxic phenotype, that is not observed in the presence of PrP C . 24 Collectively, this indicates that PrP C may act in a protective capacity and in contrast, certain abnormal forms of PrP are "toxic", promoting much more injury to various elements of the CNS and PNS than outright absence of wild-type PrP C .…”
mentioning
confidence: 99%